Pengaruh Fear of Missing Out (FOMO) dan Viral Marketing yang Ditimbulkan oleh Tiktok Terhadap Keputusan Pembelian Gadget Terbaru di Kalangan Mahasiswa Kota Malang - Enjelika, Enjelika; Zagladi, Arief Noviarakhman (BUDGETING : Journal of Business, Management and Accounting, 2025)
This research aims to analyze the influence of Fear of Missing Out (Fomo) and viral marketing caused by TikTok on students' decisions to purchase the latest gadgets in Malang City. This research uses quantitative methods and descriptive research type. The sampling technique uses non-probability sampling and is carried out using purposive sampling. The sample in this research were active Malang City students who used the TikTok application. The data collection technique uses a questionnaire. The data obtained were analyzed using the multiple regression analysis method with the help of the SPSS program.   Keywords: Fear Of Missing Out (Fomo), Purchase Decisions, Viral Marketing